Fractional Ostrowski type inequalities for functions whose mixed derivatives are prequasiinvex functions. Issue 6 (18th August 2019) - Meftah, B.; Merad, M.; Souahi, A.
Abstract: In this paper, the class of co-ordinated prequasiinvex functions is introduced, a new identity involving functions of two variable is establshed, some new fractional Ostrowski type inequalities are derived.